Identification of the Novel Host Protein Interacting With the Structural Protein VP1 of Chinese Sacbrood Virus by Yeast Two-Hybrid Screening - Zhang, Xiyan; Fei, Dongliang; Sun, Li; Li, Ming; Ma, YueYu; Wang, Chen; Huang, Sichao; Ma, Mingxiao (Frontiers in Microbiology, 2019)
Chinese sacbrood virus (CSBV) is the major cause and lead to the collapse of Apis cerana colonies. VP1, the structural protein of CSBV, shows the highest variation in the amino acid sequences among proteins from different CSBV strains as well as exhibits excellent immunogenicity. However, its function with host protein still remains unclear. To clarify its function with host protein, we screened out host cellular proteins that interact with VP1 using the membrane protein yeast two-hybrid system. In addition, we verified interactions between heat shock protein 70 cognate 5 (Hsp70-c5) and VP1 using glutathione S-transferase (GST) pull-down and co-immunoprecipitation assays. VP1 and Hsp70-c5 were colocalized in the cytoplasm and nucleus. Using western blot and real-time polymerase chain reaction (PCR), Hsp70-c5 expression in CSBV-infected larvae was upregulated compared with that in healthy larvae. We observed that when we silenced Hsp70-c5, VP1 expression was significantly downregulated. These results demonstrate that Hsp70-c5 is involved in at least one stage(s) of the viral life cycle.